Polyethylene Terephthalate Microplastic Exposure Induced Reproductive Toxicity Through Oxidative Stress and p38 Signaling Pathway Activation in Male Mice - Tianyang Li; Bohao Bian; Rihao Ji; Xiuwen Zhu; Xiaohui Wo; Qiankun Song; Zhigang Li; Feifei Wang; Yuqiao Jia (Toxics)
Polyethylene terephthalate (PET) is a type of polymer plastic that is often used to make plastic bags, bottles, and clothes. However, the waste of such plastic products is decomposed into microplastics (MPs), which are plastic fragments smaller than 5 mm, by various external forces such as wind, UV radiation, mechanical wear, and biodegradation. PET MPs have been widely detected in the environment and human tissue samples; however, the toxicity and mechanism of PET MPs in mammals are still unclear. In this study, we investigated the male reproductive toxicity of PET MPs and their underlying mechanism. A total of 80 male mice were orally exposed to 0.01, 0.1, and 1 mg/d of PET MPs (with a diameter of 1 μm) for 42 days. The results showed that 1 μm PET MPs induced different degrees of pathological damage to testicular tissues, decreased sperm quality, and increased the apoptosis of spermatogenic cells via oxidative stress and p38 signaling pathway activation. To further illustrate and verify the mechanistic pathway, oxidative stress was antagonized using N-acetylcysteine (NAC), and the activation of the p38 signaling pathway was blocked using SB203580. The results revealed that the male reproductive injury effects after exposure to PET MPs were significantly ameliorated. Specifically, the testicular tissue lesions were relieved, the sperm quality improved, and the apoptosis of spermatogenic cells decreased. These results demonstrated that PET MP exposure induced male reproductive toxicity through oxidative stress and the p38 signaling pathway. This study provides new insights into the reproductive toxicity of MPs in males, as well as valuable references for public health protection strategies.